A kind of machine-made sand self-compacting concrete and its preparation method and construction process

By optimizing the particle size ratio of machined sand and coarse aggregate, the fluidity and crack resistance of self-contained concrete are improved, the construction quality problems in tunnel projects are solved, the cost and shrinkage rate are reduced, and efficient and safe tunnels are achieved Second lining construction.

CN116639919BActive Publication Date: 2024-12-13中交四航局第六工程有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310482350.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-30
Publication Date
2024-12-13
Estimated Expiration
2043-04-30

AI Technical Summary

Technical Problem

The existing anchor spray concrete construction method in tunnel projects is prone to quality problems such as air leakage, untight structure, cracks, and water leakage during the second lining construction process, resulting in safety hazards. Moreover, traditional self-finished concrete has a high cost and a large shrinkage rate, making it difficult to be widely used. application.

Method used

Self-finished concrete based on machine sand is used, and its raw materials include gel, aggregate, water and additives. The water-cement ratio of gel is 0.335~0.345, the sand rate is 50%~53.5%, and the coarse aggregate contains fine crushing. Stone and coarse gravel can improve fluidity and crack resistance by optimizing particle size ratio and gel material usage, and reduce costs.

Benefits of technology

It realizes concrete that can be filled tightly without vibration, reduces cost and shrinkage, improves compressive strength and fluidity, and is suitable for tunnel second lining construction, solving the application limitations of traditional self-finished concrete in tunnel engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application provides a machine-made sand self-compacting concrete and a preparation method and construction process thereof, which relate to the technical field of building materials. The raw materials of the concrete include cementitious material, aggregate, water and additives; wherein the cementitious material in the raw materials is not higher than 22.3% and not lower than 21.5%, and the water-cement ratio of the cementitious material to the water is 0.335-0.345; the aggregate includes sand and coarse aggregate; the sand is machine-made sand, and the sand rate is not lower than 50% and not higher than 53.5%; the coarse aggregate includes fine crushed stone with a D90 of 5-10 mm and coarse crushed stone with a D90 of 10-20 mm; and the water consumption of each cubic meter of the concrete is 179-181 m3. 3 The present application also provides a preparation method and a construction process of the concrete. The concrete provided by the present application improves the defect that the self-compacting concrete in the prior art can only use natural sand as aggregate and it is difficult to meet the requirements by using machine-made sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a machine-made sand self-compacting concrete and a preparation method and construction process thereof. Background Art

[0002] The New Austrian Tunneling Method (NATM) is one of the most widely used and mature construction methods in tunnel construction at home and abroad. The principle of this method is to use anchor sprayed concrete as the initial support after tunnel excavation, and use cast-in-place concrete as the secondary lining for the inner layer. The primary support and the secondary lining form a composite lining structure, and a waterproof board is set between the two linings. However, this construction method is prone to quality problems such as voids, loose structures, cracks, water leaks, and poor appearance quality during the construction of the secondary lining, which in turn brings safety hazards. In order to solve this technical problem, the researchers proposed a self-compacting concrete with high fluidity and the ability to achieve dense filling without vibration. This concrete can rely on good fluidity and permeability to penetrate every corner of the steel bar-filled formwork. It is a high-performance concrete with unique advantages in the construction of the secondary lining. Summary of the invention

[0003] The purpose of the present application is to provide a machine-made sand self-compacting concrete and its preparation method and construction process, which improves the technical problems in the prior art that the self-compacting concrete requires a large amount of cementitious materials and needs river sand for configuration, resulting in high cost and large shrinkage rate.

[0004] To achieve the above objectives, this application provides the following technical solutions:

[0005] The present application provides a self-compacting concrete based on machine-made sand, the raw materials of which include cementitious material, aggregate, water and additives;

[0006] The content of the agglomerate in the raw material is not higher than 22.3% and not lower than 21.5%, and the water-cement ratio of the agglomerate to the water is 0.335-0.345;

[0007] The aggregate includes sand and coarse aggregate; the sand is machine-made sand, with a sand ratio of not less than 50% and not more than 53.5%; the coarse aggregate includes fine crushed stone with a D90 of 5-10 mm and coarse crushed stone with a D90 of 10-20 mm; and the water consumption of each cubic meter of the concrete is 179-181 m3. 3 .

[0008] Furthermore, in some embodiments of the present application, the cementitious material comprises cement, Class F Grade I fly ash and limestone powder; in the cementitious material, the ratio of the cement, fly ash and stone powder is (65~55%): (30~35%): (5~10%) by mass fraction.

[0009] Furthermore, in some embodiments of the present application, the mass ratio of the coarse crushed stone to the fine crushed stone is (4:6) to (5:5).

[0010] Furthermore, in some embodiments of the present application, the auxiliary agent includes a water reducing agent; in the raw material, the content of the auxiliary agent is 0.2% to 0.3% by mass.

[0011] Further, in some embodiments of the present application, the 500mm expansion time obtained by the T500 test of the concrete mixture is not higher than 6s, the slump expansion is not lower than 655mm, and the difference between the shedding expansion and the J-ring expansion is not higher than 75mm;

[0012] The outflow time of the concrete mixture obtained by the V-funnel fluidity test is not more than 80 seconds;

[0013] The height difference of the concrete mixture obtained by the U-box filling test is not higher than 30 mm;

[0014] The height ratio of the concrete mixture obtained by the L-box penetration test is not less than 0.75;

[0015] Moreover, the 28d compressive strength of the concrete formed after the concrete mixture is solidified is not less than 35MPa; and the 28d shrinkage rate of the concrete formed after the concrete is solidified is not higher than 0.15%.

[0016] Furthermore, in some embodiments of the present application, the self-compacting concrete includes the following raw materials in the following mass fractions:

[0017] Cement 286-312 parts, fly ash 156-182 parts, limestone powder 26-52 parts, fine aggregate 854 parts, coarse aggregate 789 parts, water 180 parts, water reducer 5.2 parts;

[0018] Among them, the mass ratio of the coarse crushed stone with D90 of 10-20 mm and the fine crushed stone with D90 of 5-10 mm in the coarse aggregate is (4:6)-(5:5), and the sum of the mass fractions of the cement, fly ash and limestone is 510-530 parts.

[0019] In a second aspect, the present application also provides a method for preparing a slurry of a self-compacting concrete based on machine-made sand, comprising mixing the raw materials described in the first aspect and mixing them uniformly within 5 minutes.

[0020] In a third aspect, the present application further provides a construction process for self-compacting concrete based on machine-made sand, which uses the raw materials described in the first aspect to mix and form a concrete mixture;

[0021] The concrete mixture is poured into the construction site where the concrete mixture is to be poured within 45 minutes.

[0022] The present application provides a self-compacting concrete based on machine-made sand, a preparation method and a construction process. The self-compacting concrete uses machine-made sand with lower cost and more edges as fine aggregate, which reduces the cost and shrinkage of traditional self-compacting concrete using natural sand, and also reduces the use of cementitious materials, further reduces the cost of self-compacting concrete, and improves the defect of poor crack resistance of self-compacting concrete in the prior art; at the same time, in order to solve the defect of poor fluidity of machine-made sand compared with natural sand, the present application optimizes the particle size ratio and dosage ratio of coarse aggregate and fine aggregate, so that its fluidity can meet the needs of self-compacting concrete; at the same time, since the amount of cementitious materials required for the self-compacting concrete provided by the present application is relatively low, the viscosity of the self-compacting concrete mixture is controlled, and its filling, workability and penetration are optimized, so that the self-compacting concrete mixture is not only easier to fill and does not require vibration, but also has the effect of controlling the protective layer of steel bars. The self-compacting concrete based on machine-made sand provided by the present application is suitable for concrete for tunnel engineering and other construction concrete; in particular, it is suitable for concrete for tunnel secondary lining construction. DETAILED DESCRIPTION

[0023] The following will clearly and completely describe the present application scheme in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0024] Since self-compacting concrete has high requirements on fluidity in order to achieve the effect of filling and compaction without vibration, the sand used in the prior art is usually natural sand with better fluidity. However, due to the non-renewability of natural sand, its cost is high and it is difficult to purchase; at the same time, in order to achieve high fluidity, self-compacting concrete using natural sand usually has a high sand ratio and a high amount of cementitious materials, which leads to large shrinkage of concrete and insufficient crack resistance, thus limiting its application in tunnel secondary lining projects.

[0025] In this regard, the inventor provides a self-compacting concrete based on machine-made sand, the raw materials of which include cementitious material, aggregate, water and additives;

[0026] The content of the agglomerate in the raw material is not higher than 22.3% and not lower than 21.5%, and the water-cement ratio of the agglomerate to the water is 0.335-0.345;

[0027] The aggregate includes sand and coarse aggregate; the sand is machine-made sand, with a sand ratio of not less than 50% and not more than 53.5%; the coarse aggregate includes fine crushed stone with a D90 of 5-10 mm and coarse crushed stone with a D90 of 5-10 mm; and the water consumption of each cubic meter of the concrete is 179-181 m 3 .

[0028] Artificial sand refers to sand processed by sand making machines and other auxiliary equipment. Its shape is more irregular than natural sand formed by long-term impact, and its particle size distribution is difficult to form the natural gradation of natural sand. When used, it usually requires higher adhesion and a higher amount of cementitious materials. At the same time, because artificial sand has not been impacted by water for many years, its compressive strength is usually slightly worse than that of natural sand.

[0029] In the present application, the inventors use the particle size and content of machine-made sand and coarse aggregate to adjust the combination, overcome the defect of poor fluidity of machine-made sand, and at the same time, under the premise of increasing the sand ratio, give play to the advantage of aggregate in enhancing crack resistance, so that the self-compacting concrete obtained has not only good fluidity but also better crack resistance; in addition, the content of cementitious material in the self-compacting concrete provided by the present application is low, which is conducive to extending the construction time of the concrete mixture and facilitating construction; at the same time, it can also reduce the shrinkage rate of concrete, making it less prone to cracks, water leakage and other quality problems. It should be noted that in the present application, cementitious material refers to a material that can be transformed from a slurry into a solid stone-like body under physical and chemical effects, and can cement other materials to make a composite solid with a certain mechanical strength. Specifically, it is a raw material in the concrete raw material that has the activity to undergo chemical reactions such as hydration reaction, such as cement, limestone, fly ash, and mineral powder.

[0030] It should be noted that in the present application, the content of cementitious material should not be too high or too low. Too low cementitious material is difficult to provide sufficient bonding performance and will also affect the quality of concrete. Exemplarily, the content of cementitious material in the raw material is 21.5%, 21.6%, 21.7%, 21.8%, 21.9%, 22.0%, 22.1%, 22.2%, and 22.3%; further preferably, 21.9% to 22.2%; and most preferably, 22.1%. At the same time, in the raw materials of concrete provided in the present application, the value of the sand ratio should not be too high or too low. Although the increase in the sand ratio is conducive to filling the gaps between coarse aggregates and improving the fluidity of concrete; however, too high a sand ratio will lead to a decrease in the compactness of concrete, reduce the permeability of concrete, and cause its working performance to decrease, which is not conducive to the wrapping of the concrete mixture on the steel bars. For example, the sand ratio of machine-made sand in the raw material can be 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%; more preferably, 51% to 53%; and most preferably, 52%. In addition, it should be further explained that the particle size selection and proportion of fine crushed stone and coarse crushed stone in the coarse aggregate used in this application should also be limited to the above range, so that the machine-made fine crushed stone can be filled in the gaps between the coarse crushed stones to improve the fluidity of the concrete, while avoiding the increase of gaps and collisions between the fine crushed stones, improving the porosity of the concrete, and thus affecting the compactness and compressive strength of the concrete. In addition, it can also improve the decrease in the passability of the concrete mixture caused by the increase in porosity due to the fine crushed stone.

[0031] In the concrete provided in the present application, the above-mentioned limitations on sand ratio, machine-made sand and cementitious materials and the addition of additives are indispensable, so that machine-made sand can be used in self-compacting concrete and the quality requirements of tunnel secondary lining construction such as no voids, no cracks, no water leakage and good compactness can be achieved, thereby solving the technical problem in the prior art that self-compacting concrete, especially self-compacting concrete based on machine-made sand, is difficult to be widely used in tunnel secondary lining construction.

[0032] In some embodiments, the machine-made sand used in the present application can be commercially available stone powder with a mass fraction of 12-13%, a fineness modulus of not less than 3.0, a porosity of 41-42%, and an apparent density of not less than 2700 kg / m 3 For example, the machine-made sand has an apparent density of 2720 kg / m 3 , porosity 41.4%, mud content 0.1%, fineness modulus 3.0, methylene blue MB value 0.8g / kg, stone powder content 12.6%, maximum crushing index 12% of machine-made sand.

[0033] In some embodiments, the fine crushed stone in the coarse aggregate used in the present application may have a porosity higher than that of machine-made sand, such as 45%, and an apparent density of not less than 2700 kg / m 3 , fine crushed stone with a mass fraction of needle-like particles not less than 3% and not more than 4%; and coarse crushed stone with a porosity higher than that of machine-made sand, such as 45%, and an apparent density of not less than 2700kg / m 3 , coarse crushed stone with a mass fraction of needle-like particles of not less than 5% and not more than 6%. For example, the apparent density of the fine crushed stone is 2714 kg / m 3 , bulk density is 1490kg / m 3 The porosity is 45%, the mud content is 1.8%, the mud block content is 0.2%, the needle-like particles are 3.7%, and the apparent density of the coarse crushed stone is 2710kg / m 3 , bulk density is 1490kg / m 3 The porosity is 45%, the mud content is 2.6%, the mud block content is 0.3%, and the needle-like particles are 5.1%.

[0034] Furthermore, the sieve residue of more than 4.75 mm in the machine-made sand used in this application is not higher than 1%, and the sieve residue of less than 0.15 mm does not exceed 20%; the sieve residue of less than 4.75 mm in the fine crushed stone used in this application is not less than 80%; the sieve residue of more than 9.5 mm is not higher than 1%. The sieve residue of less than 9.5 mm in the coarse crushed stone used in this application is not less than 90%, and the sieve residue of more than 19 mm is not higher than 1%. Therefore, the particle size distribution of fine crushed stone and coarse crushed stone in the coarse aggregate used in this application is bimodal; the particle size distribution of coarse aggregate and machine-made sand is trimodal, so as to achieve the effect that the fine crushed stone fills the gap between the coarse crushed stone, and the machine-made sand fills the gap between the fine crushed stone and the coarse crushed stone, thereby improving the fluidity and density of the concrete mixture, and improving the porosity and permeability of the concrete.

[0035] In some embodiments, the cementitious material comprises cement, Class F Grade I fly ash and limestone powder; in the cementitious material, the ratio of the cement, fly ash and stone powder is (65-55%): (30-35%): (5-10%) by mass fraction. The cement described in the present application is preferably a silicate cement having a 28d compressive strength of not less than 47MPa and a 28d flexural strength of not less than 7.5Mpa. For example, it can be Yuehai P·O42.5R cement produced by Lechang Zhongjiancai Cement Co., Ltd., which has a specific surface area of ​​320㎡ / kg and a density of 3030kg / m 3, the standard consistency water consumption is 27%, the initial setting time is 142min, the final setting time is 241min, the 28d compressive strength is 47.8MPa, and the 28d flexural strength is 7.8MPa. In addition, the fly ash used in this application can be a Class I fly ash with a fineness of not less than 21.5% and a loss on ignition between 1.7 and 1.9%; illustratively, the fly ash is selected from the Class I fly ash of Gongyi Yuanheng Water Purification Material Factory, with a fineness of 21.6%, a water demand ratio of 102%, and a loss on ignition of 1.76%. The limestone powder used in this application is a stone powder with a calcium carbonate content of not less than 97%, a fineness of not less than 11%, and a fluidity ratio higher than 96%. For example, the limestone powder is the limestone powder of Gongyi Yuanheng Water Purification Material Factory, with a calcium carbonate content of 97.36%, a fineness of 11.3%, a fluidity ratio of 97%, and a water content of 0.2%.

[0036] It should be noted that the cement in the cementitious material is of high grade to improve the adhesiveness of the cementitious material; however, the grade of the cement should not be too high to avoid its hardening speed being too fast and its shrinkage being too large, which is not conducive to its use in tunnel construction. Similarly, the fineness and ignition loss rate of fly ash also need to be limited within the above range, so that it can be well filled between cement particles to reduce the viscosity of the concrete mixture, thereby improving the fluidity of the concrete; at the same time, it can maintain a certain activity, so that it can react with the hydration product of cement to improve the strength of the concrete. In addition, the amount of fly ash added should not be too high to avoid the early strength of the concrete being reduced due to insufficient cement addition. In addition, too high a doping amount of fly ash may also increase the viscosity of the concrete mixture, which is not conducive to improving the fluidity of the concrete mixture. In addition, the surface of fly ash is usually easy to adhere to gas (the fly ash formed by burning is often porous or has a number of depressions on the surface that are easy to accommodate gas). Therefore, the addition of fly ash will also add the gas contained in the fly ash. If the amount of fly ash added is large, the bubble content in the concrete will be large, which is easy to cause the density and strength of the concrete. In addition, the chloride ion content in the fly ash may also increase due to the increase in the amount of fly ash added, thereby affecting the durability of the concrete. Therefore, in this application, the amount of fly ash added does not exceed 36%, preferably 30~35%, and more preferably 35%; so that the gas content in the concrete is not higher than 6%, and the chloride ion content is not higher than 0.06%. In fact, when the amount of fly ash added exceeds 35%, the performance of the concrete will begin to decline. The amount of limestone powder added should not be too high. Excessive limestone powder is easy to increase the viscosity of the concrete mixture, which is not conducive to its fluidity and passability, and is also not conducive to its construction. The limestone powder used in this application can be recycled powder from the process of machine-made sand processing, or other commercially available limestone powder, which has the characteristics of rounded particles and smooth surface. Limestone powder is a cementitious material that replaces part of the appropriate amount of cement and is added to self-compacting concrete. It can increase the content of fine powder in concrete, improve the working performance of self-compacting concrete, and effectively reduce the self-shrinkage deformation of concrete. It can further replace chemical rheology modifiers, so that the concrete provided by this application can meet the performance requirements of self-compacting concrete without adding chemical rheology modifiers. In addition, the fineness of the limestone powder used in this application is lower than that of cement and fly ash, so that it can be used as a fine aggregate to fill the particle size difference between cement, fly ash and other cementitious materials and fine aggregates, and optimize the rheological properties of the concrete system; at the same time, it can also reduce the yield value of concrete, so that its yield stress is not higher than 425Pa; and maintain a large fluidity of concrete without stratification.

[0037] The viscosity of the concrete mixture formed by mixing the raw materials needs to be controlled within the range of 9-11 Pa·s.

[0038] The viscosity of the concrete mixture does not change much during the process from mixing to pouring, which is conducive to ensuring the fluidity, filling and penetration of the concrete mixture during the pouring process, so that the 500mm expansion time of the concrete mixture obtained by the T500 test is not higher than 6s, the slump expansion is not lower than 655mm, and the difference between the shedding expansion and the J-ring expansion is not higher than 75mm;

[0039] The outflow time of the concrete mixture obtained by the V-funnel fluidity test is not more than 80 seconds;

[0040] The height difference of the concrete mixture obtained by the U-box filling test is not higher than 30 mm;

[0041] The height ratio of the concrete mixture obtained by the L-box penetration test is not less than 0.75;

[0042] Moreover, the 28d compressive strength of the concrete formed after the concrete mixture is solidified is not less than 35MPa, and can reach above 51MPa; and the 28d shrinkage rate of the concrete formed after the concrete is solidified is not higher than 0.15%.

[0043] In some embodiments, the auxiliary agent includes a water reducing agent; in the raw material, the content of the auxiliary agent is 0.2-0.3% by mass, preferably 0.2%-0.25% by mass.

[0044] In some embodiments, the self-compacting concrete comprises the following raw materials in the following mass fractions:

[0045] Cement 286-312 parts, fly ash 156-182 parts, limestone powder 26-52 parts, fine aggregate 854 parts, coarse aggregate 789 parts, water 180 parts, water reducer 5.2 parts;

[0046] Among them, the mass ratio of the coarse crushed stone with D90 of 10~20mm and the fine crushed stone with D90 of 5~10mm in the coarse aggregate is (4:6)~(5:5), and the sum of the mass fractions of the cement, fly ash and limestone is 510~530 parts. Preferably, the sum of the mass fractions of the cement, fly ash and limestone is 520 parts.

[0047] In a second aspect, the present application also provides a method for preparing a slurry of a self-compacting concrete based on machine-made sand, comprising mixing the raw materials described in the first aspect and mixing them uniformly within 5 minutes.

[0048] In a third aspect, the present application further provides a construction process for self-compacting concrete based on machine-made sand, which uses the raw materials described in the first aspect to mix and form a concrete mixture;

[0049] The concrete mixture is poured into the construction site where the concrete mixture is to be poured within 45 minutes.

[0050] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of a self-compacting concrete based on machine-made sand provided in the embodiments of the present application, the above technical solution is illustrated by way of examples below.

[0051] The cement used in the following examples is Yuehai brand P·O42.5R cement produced by Changzhou Zhongjiancai Cement Co., Ltd., with a specific surface area of ​​320 m2 / kg and a density of 3030 kg / m 3 , standard consistency water consumption is 27%, initial setting time is 142min, final setting time is 241min, 28d compressive strength is 47.8MPa, 28d flexural strength is 7.8Mpa; fly ash uses Grade I fly ash from Gongyi Yuanheng Water Purification Material Factory, with fineness of 21.6%, water requirement ratio of 102%, and loss on ignition of 1.76%. Limestone powder uses limestone powder from Gongyi Yuanheng Water Purification Material Factory, with a calcium carbonate content of 97.36%, fineness of 11.3%, fluidity ratio of 97%, and water content of 0.2%; the water reducer uses the polycarboxylic acid high-performance water reducer from Suzhou Fuke Technology Co., Ltd., with a water reduction rate of 25.6%, a water seepage rate of 29%, an air content of 2.9%, a solid content of 17.53%, and a slump change of 50mm over 1h; the machine-made sand is produced by a jaw crusher in a local stone field, and the particle shape is not as good as that produced by the impact crusher, and the angularity is poor. The apparent density of the machine-made sand is 2720kg / m 3 , porosity 41.4%, mud content 0.1%, fineness modulus 3.0, methylene blue MB value 0.8g / kg, stone powder content 12.6%, maximum crushing index 12%; its grading table is shown in Table 1:

[0052] Table 1

[0053]

[0054] The coarse aggregate is produced by a jaw crusher in a local stone field. The crushed stone is 5mm~10mm and the apparent density is 2714kg / m 3 , bulk density 1490kg / m 3 , porosity 45%, mud content 1.8%, mud block content 0.2%, needle-like particles 3.7%, and gradation as shown in Table 2. Crushed stone 10mm~20mm apparent density 2710kg / m 3 , bulk density 1490kg / m 3, porosity 45%, mud content 2.6%, mud block content 0.3%, needle-like particles 5.1%, and its gradation table is shown in Table 2:

[0055] Table 2

[0056]

[0057] In order to verify the performance of the self-compacting concrete based on machine-made sand provided in the present application, the inventors provide the following examples and comparative examples:

[0058] Example 1

[0059] The present application provides a self-compacting concrete based on machine-made sand, which includes the following raw materials in parts by mass:

[0060] 286 parts of cement, 182 parts of fly ash, 52 parts of limestone powder, 854 parts of fine aggregate, 789 parts of coarse aggregate, of which the mass ratio of fine crushed stone with D90 of 5-10mm and coarse crushed stone with D90 of 10-20mm in coarse aggregate is 6:4, 180 parts of water, 5.2 parts of water reducer. The water-cement ratio of the concrete is 0.34, the mass fraction of cementitious material is 520 parts, and the sand ratio is 52%.

[0061] Example 2

[0062] The present application provides a self-compacting concrete based on machine-made sand, which includes the following raw materials in parts by mass:

[0063] 286 parts of cement, 182 parts of fly ash, 52 parts of limestone powder, 854 parts of fine aggregate, 789 parts of coarse aggregate, of which the mass ratio of fine crushed stone with D90 of 5-10mm and coarse crushed stone with D90 of 10-20mm in coarse aggregate is 5:5, 180 parts of water, 5.2 parts of water reducer. The water-cement ratio of the concrete is 0.34, the mass fraction of cementitious material is 520 parts, and the sand ratio is 52%.

[0064] Example 3

[0065] The present application provides a self-compacting concrete based on machine-made sand, which includes the following raw materials in parts by mass:

[0066] 312 parts of cement, 182 parts of fly ash, 26 parts of limestone powder, 854 parts of fine aggregate, 789 parts of coarse aggregate, of which the mass ratio of fine crushed stone with D90 of 5~10mm and coarse crushed stone with D90 of 10~20mm in coarse aggregate is 5:5, 180 parts of water, 5.2 parts of water reducer. The water-cement ratio of the concrete is 0.34, the mass fraction of cementitious material is 520 parts, and the sand ratio is 52%.

[0067] Example 4

[0068] The present application provides a self-compacting concrete based on machine-made sand, which includes the following raw materials in parts by mass:

[0069] 312 parts of cement, 156 parts of fly ash, 52 parts of limestone powder, 854 parts of fine aggregate, 789 parts of coarse aggregate, of which the mass ratio of fine crushed stone with D90 of 5-10mm and coarse crushed stone with D90 of 10-20mm in coarse aggregate is 5:5, 180 parts of water, 5.2 parts of water reducer. The water-cement ratio of the concrete is 0.34, the mass fraction of cementitious material is 520 parts, and the sand ratio is 50%.

[0070] In order to verify the performance of the self-compacting concrete provided in the present application, the inventors also provided the following comparative examples, in which the proportions of the raw materials in the comparative examples are shown in Table 3:

[0071] Table 3

[0072]

[0073] The sand used in Comparative Example 20 (D20) is natural river sand with an apparent density of 2.61 kg / m 3 , bulk density 1.46g / cm 3 The porosity is 40%, the mud content is 1.5%, and the fineness modulus is 2.8.

[0074] The concrete mixtures obtained in the above examples and comparative examples were tested for working performance and mechanical properties, and the specific test methods or test parameters are as follows:

[0075] T500 Test

[0076] The test is carried out in accordance with the slump spread and T500 flow time test methods in Appendix A of the Guidelines for Design and Construction of Self-Compacting Concrete (CCES 02-2004). The test measures the time required for the concrete mixture to flow to 500 mm (T500); measures the maximum diameter of the expanded surface of the concrete mixture and the diameter perpendicular to the maximum diameter when the concrete mixture stops spreading or the diffusion duration reaches 50 seconds, and calculates their average value (slump spread); and measures the average value of the two diameters perpendicular to each other on the expanded surface after the slump and spread of the concrete mixture stops (J-ring spread).

[0077] V-funnel test

[0078] The test was carried out in accordance with the T0534-2020 V-funnel test method for cement concrete mixtures in the "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020).

[0079] Place a material container under the discharge port of the V-shaped funnel; after the funnel is filled with the sample and left to stand for 10s±2s, open the sealing cover of the discharge port of the funnel and use a stopwatch to measure the time from opening the cover to the time when all the concrete mixture in the funnel flows out.

[0080] U-box test

[0081] The test is carried out in accordance with the CU type test method in Appendix of the "Guidelines for Design and Construction of Self-Compacting Concrete" (CCES 02-2004).

[0082] L-type instrument test

[0083] The test is carried out in accordance with the BL type instrument test method in Appendix BL of the Guidelines for Design and Construction of Self-Compacting Concrete (CCES 02-2004).

[0084] The self-compacting concrete L-type instrument is an L-shaped box made of steel plates, which is equipped with partition doors and detachable steel mesh.

[0085] Add concrete mixture into the vertical part of the L-shaped box, let it stand for 1 minute, pull up the valve, and the concrete will flow from the vertical part through the obstacle to the horizontal part. Measure the time it takes for the concrete to flow through the steel mesh to 200mm and 400mm, and measure the height of the concrete mixture on both sides of the steel mesh. The heights are represented as H1 (close to the vertical part) and H2 (away from the vertical part).

[0086] 28d compressive strength

[0087] The test was carried out in accordance with the T0553-2005 Cement Concrete Compressive Strength Test Method in the "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020).

[0088] 28d rebound strength after demoulding

[0089] The test is carried out and the strength is converted in accordance with the Technical Specification for Testing Concrete Compressive Strength by Rebound Method (JGJ / T 23-2011).

[0090] The test results are shown in Table 5:

[0091] Table 5

[0092]

[0093] As can be seen from Table 5, through comparative example 1 (D1), comparative example 2 (D2), and comparative example 17 (D17), it is found that the concrete obtained by using 520 kg / m³ of cementitious material has better performance. When the amount of cementitious material is lower than 510 kg / m³, such as when the amount of cementitious material is 494 kg / m³, the fluidity and passability of the obtained concrete are poor. The amount of cementitious material should not be too large. For example, when the amount of cementitious material is increased to 550 kg / m³, although the concrete has better passability, it is too viscous, the concrete dries quickly, and the slump loss over time is too large, combined with cost factors.

[0094] In addition, by comparing the concrete of Comparative Example 1 (D1), Comparative Example 2 (D2), Comparative Example 4 (D4), Comparative Example 5 (D5), Comparative Example 9 (D9), Comparative Example 18 (D18), Comparative Example 19 (D19) and Examples 1 to 3, it was found that as the proportion of fine crushed stone (crushed stone gradation) increased, the passability of the obtained concrete became better, but the proportion of fine crushed stone should not be too high. When the ratio of fine crushed stone to coarse aggregate in the coarse aggregate reached 6:4, the working performance of the concrete began to decline and the overall strength of the concrete declined.

[0095] It can be known from the concrete of Comparative Example 1 (D1), Comparative Example 3 (D3), Comparative Example 4 (D4), Comparative Example 5 (D5), Comparative Example 6 (D6), Comparative Example 7 (D7), Comparative Example 8 (D8), Comparative Example 9 (D9), Comparative Example 10 (D10) and Examples 1 to 3 that the sand ratio of the raw material is preferably 52%, and the sand ratio should not be too high or too low. When the sand ratio is too high, such as reaching 54%, the working performance of the concrete mixture decreases rapidly and the encapsulation becomes poor.

[0096] It can be known from Comparative Example 5 (D5), Comparative Example 6 (D6), Comparative Example 9 (D9), Comparative Example 12 (D12), Comparative Example 14 (D14), Comparative Example 16 (D16) and Examples 1 to 3 that the amount of limestone powder added in the raw materials improves the performance of concrete, but the amount should not be too large. For example, when the amount of limestone powder added in the cementitious material is greater than 10%, such as 76 kg / m³ of limestone powder added in 520 kg / m³ of cementitious material, the working performance of the obtained concrete mixture deteriorates and the concrete mixture is too viscous; and when the amount of limestone powder added in the cementitious material is less than 5%, the improvement of the performance of the concrete by the limestone powder is not obvious and it is difficult to achieve the corresponding effect.

[0097] It can be known from Comparative Example 6 (D6), Comparative Example 9 (D9), Comparative Example 11 (D11), Comparative Example 13 (D13), Comparative Example 15 (D15), Comparative Example 16 (D16), Comparative Example 17 (D17) and Examples 1 to 3 that the fly ash dosage should not be too high. When the fly ash dosage in the cementitious material is higher than 35%, the working performance of the concrete decreases, water seepage occurs, and various properties are unstable. Therefore, it is better to select the dosage of fly ash in the cementitious material to be 30% to 35%.

[0098] In addition, the inventors conducted a cast-in-place lining casting test on the concrete mixtures provided in the above-mentioned Examples 1, 2, 3, 4 and Comparative Example 20 (D20), and the time from the mixing and mixing of the concrete mixture to the start of casting was controlled within 45 minutes; after 28 days, the compressive strength, rebound strength after demolding, and shrinkage rate were tested, and the surface morphology and water seepage of the formed concrete were observed. The measurement results are shown in Table 6:

[0099]

[0100] As can be seen from Table 6, Example 1, Example 2, Example 3, and Example 4 have good apparent quality, no honeycomb, no pockmarks, no voids, smooth surface, slight water bleeding, and high 28d rebound test strength, which can meet construction requirements.

[0101] In summary, the present application provides a self-compacting concrete based on machine-made sand, which has excellent compressive strength and small shrinkage, and the concrete mixture formed by the raw materials used has excellent fluidity, filling, workability and penetrability, so that it can better penetrate the steel network in the tunnel secondary lining project, and realize the formation of dense filling without vibration, so that it has high casting efficiency and good filling property, which expands the application limitations of self-compacting concrete in tunnel secondary lining projects in the prior art and eliminates the human factor errors and mistakes caused by workers' vibration construction; at the same time, because it uses machine-made sand as fine aggregate and the amount of cementitious material used is low, its cost is low, fine aggregate is easy to obtain, and it is easy to promote and apply. At the same time, it expands the application scope of machine-made sand and reverses the stereotype that machine-made sand is difficult to use in self-compacting concrete.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A self-compacting concrete based on machine-made sand, characterized in that: Its raw materials include cementitious materials, aggregates, water and additives; Wherein, the content of the agglomerate in the raw material is not higher than 22.3% and not lower than 21.5%, and the water-to-binder ratio of the agglomerate to the water is 0.335-0.345; The aggregate includes sand and coarse aggregate; the sand is machine-made sand with a sand ratio of not less than 52% and not more than 53.5%; the coarse aggregate includes fine crushed stone with a D90 of 5-10 mm and coarse crushed stone with a D90 of 10-20 mm; and the water consumption of each cubic meter of the concrete is 179-181 m 3 ; The raw materials are mixed to form a concrete mixture, and the concrete mixture formed after solidification has a 28d compressive strength of not less than 35MPa; and the concrete formed after solidification has a 28d shrinkage rate of not more than 0.15%.

2. The self-compacting concrete based on machine-made sand according to claim 1, characterized in that: The cementitious material comprises cement, Class F Grade I fly ash and limestone powder; in the cementitious material, the ratio of the cement, fly ash and limestone powder is (65-55%): (30-35%): (5-10%) by mass fraction.

3. The self-compacting concrete based on machine-made sand according to claim 1, characterized in that: The mass ratio of the coarse crushed stone to the fine crushed stone is (4:6) to (5:5).

4. The self-compacting concrete based on machine-made sand according to claim 1, characterized in that: The auxiliary agent includes a water reducing agent; in the raw material, the content of the auxiliary agent is 0.2-0.3% by mass.

5. The self-compacting concrete based on machine-made sand according to any one of claims 1 to 4, characterized in that: The self-compacting concrete comprises the following raw materials in the following mass parts: Cement 286-312 parts, fly ash 156-182 parts, limestone powder 26-52 parts, fine aggregate 854 parts, coarse aggregate 789 parts, water 180 parts, water reducer 5.2 parts; Among them, the mass ratio of the coarse crushed stone with D90 of 10~20mm and the fine crushed stone with D90 of 5~10mm in the coarse aggregate is (4:6)~(5:5); and the sum of the mass parts of the cement, fly ash and limestone is 510~530 parts.

6. A method for preparing slurry for self-compacting concrete based on machine-made sand, characterized in that: Mix the raw materials according to any one of claims 1 to 5 and mix them evenly within 5 minutes.

7. A construction process for self-compacting concrete based on machine-made sand, characterized in that: Mixing the raw materials according to any one of claims 1 to 5 to form a concrete mixture; The concrete mixture is poured into the construction site where the concrete mixture is to be poured within 45 minutes.

Citation Information

Patent Citations

  • Vibration-free self-compacting concrete composition

    CN102951876A

  • Machine-made sand self-compacting concrete

    CN113135707A